NEW EVIDENCE OF THE EARLIEST DOMESTIC DOGS IN THE AMERICAS. Issue 1 (26th December 2018) - Perri, Angela; Widga, Chris; Lawler, Dennis; Martin, Terrance; Loebel, Thomas; Farnsworth, Kenneth; Kohn, Luci; Buenger, Brent
Abstract : The domestication of dogs likely occurred in Eurasia by 16, 000 years ago, and the initial peopling of the Americas potentially happened around the same time. Dogs were long thought to have accompanied the first migrations into the Americas, but conclusive evidence for Paleoindian dogs is lacking. In this study, the direct dating of two dogs from the Koster site (Greene County, Illinois) and a newly described dog from the Stilwell II site (Pike County, Illinois) to between 10, 190 and 9, 630 cal BP represents the earliest confirmed evidence of domestic dogs in the Americas and individual dog burials anywhere in the world. Analysis of these animals shows Early Archaic dogs were medium sized, lived active lifestyles, and exhibited significant morphological variation. Stable isotope analyses suggest diets dominated by terrestrial C3 resources and substantial consumption of riverine fish. Abstract : La domesticación del perro probablemente ocurrió en Eurasia hace 16, 000 años, potencialmente alrededor del mismo tiempo que el poblamiento inicial de América. Durante mucho tiempo se pensó que los perros habían acompañado las primeras migraciones humanas hacia el continente americano, pero no se ha encontrado evidencia concluyente de perros paleoindios. La datación directa de dos perros del sitio Koster (condado Greene, Illinois) y un perro recientemente descrito del sitio Stilwell II (condado Pike, Illinois) entre 10.190 y 9630 cal aP representa la evidencia confirmada más temprana de perros domésticos en América y de enterramientos individuales de perros en cualquier parte del mundo. El análisis de estos animales muestra que los perros arcaicos tempranos eran de tamaño mediano y vivían estilos de vida activos, pero que ya exhibían una variación morfológica significativa. Los análisis de isótopos estables sugieren que sus dietas estuvieron dominadas por recursos terrestres de tipo C3 y por el consumo sustancial de peces de agua dulce.